Strategi Intervensi Program dan Pemanfaatan Potensi Lokal dalam Upaya Peningkatan Cakupan ASI Eksklusif di Kabupaten Balangan - Rukmini Rukmini; Eka Fatmawati; Yuli Trisnanto; Yunita Fitrianti (Media Penelitian dan Pengembangan Kesehatan, 2020)
Abstract Exclusive breastfeeding is the initial stage in nutritional intake for children. Problems that occur because the pattern of breastfeeding is not in accordance with the concept of exclusive breastfeeding, such as providing complementary foods with breast milk (MP-ASI) earlier. This paper is a policy article, based on the results of qualitative research with a health ethnographic approach, to determine the factors that influence the low coverage of exclusive breastfeeding. The research was conducted in Mauya Village (ethnic Banjar) and Marajai Village (ethnic Dayak Meratus), Balangan District, South Kalimantan. The main informants are mothers who have babies 0-6 months (16 people), while the informants who support village midwives (2 people), traditional / community leaders (2 people) and health workers (2 people). Data collection by participant observation, in-depth interviews and unstructured interviews, audio-visual documentation and secondary data search in facilities and health workers. The results show that the practice of exclusive breastfeeding in Mauya Village and Marajai Village, Balangan Regency is still low influenced by several factors, namely aspects of maternal and infant health, availability of health care workers and facilities, social, economic, cultural, geographic conditions, access to information media. It can be concluded that there are 3 main factors, namely predisposing, enabling, and driving factors that are interrelated in the practice of exclusive breastfeeding. This article recommends that program intervention efforts to overcome the problem of exclusive breastfeeding,it is necessary to carry out comprehensive and integrated intervension both in improving the quality of health service programs, community empowerment and cross-sector cooperation and utilization of local cultural potentials. Abstrak Pemberian air susu ibu (ASI) eksklusif merupakan tahap awal dalam asupan gizi bagi anak. Permasalahan yang terjadi karena pola pemberian ASI yang tidak sesuai dengan konsep ASI eksklusif, seperti memberikan Makanan Pendamping Air Susu ibu (MP-ASI) lebih dini. Tulisan ini merupakan artikel kebijakan berdasarkan hasil penelitian kualitatif dengan pendekatan etnografi kesehatan, untuk mengetahui faktor-faktor yang memengaruhi rendahnya cakupan ASI eksklusif. Penelitian dilakukan di Desa Mauya (etnik Banjar) dan Desa Marajai (dominasi etnik Dayak Meratus), Kabupaten Balangan Kalimantan Selatan. Informan utama adalah ibu yang memiliki bayi 0-6 bulan (16 orang),sedangkan informan pendukung bidan kampung (2 orang), tokoh adat/tokoh masyarakat (2 orang) dan petugas kesehatan (2 orang). Pengumpulan data dengan participant observation, wawancara mendalam dan wawancara tidak terstrukur, dokumentasi audio visual, dan penelusuran data sekunder di fasilitas dan petugas kesehatan. Hasil menunjukkan praktik ASI eksklusif di Desa Mauya dan Desa Marajai Kabupaten Balangan masih rendah dipengaruhi beberapa faktor yaitu aspek kesehatan ibu dan bayi, ketersediaan petugas dan fasilitas pelayanan kesehatan, faktor sosial, ekonomi, budaya, kondisi geografis, akses media informasi. Dapat disimpulkan ada tiga faktor utama yakni faktor predisposisi, pemungkin, dan pendorong yang saling terkait dalam praktik ASI eksklusif. Artikel ini merekomendasikan upaya intervensi program untuk mengatasi permasalahan ASI eksklusif dilakukan secara menyeluruh, komprehensif dan terintegrasi baik pada peningkatan kualitas program pelayanan kesehatan, pemberdayaan masyarakat dan kerjasama lintas sektor serta pemanfaatan potensi budaya lokal.